1992
DOI: 10.1111/j.1365-2052.1992.tb00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical evidence of the expression of two major histocompatibility complex class I genes on bovine peripheral blood mononuclear cells

Abstract: 113 114 1. Joosten et al.expressed on normal bovine PBMC. In IEF analysis the additional use of mAb recognizing polymorphic determinants on serologically defined A-locus products highly facilitated the detection and typing of second locus products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It has been reported that N-terminus of β 2 m is involved in the formation of the W6/32 epitope (Shields and Ribaudo 1998) and in the case presented here, the N-terminal methionine of the recombinant bovine met-β 2 m likely interferes with W6/32 detection. Alternatively, the failed W6/32 recognition may be explained by the lack of pan-specificity of the antibody to BoLA-I when associated with bovine met-β 2 m (Joosten et al 1992). Substituting bovine met-β 2 m with human β 2 m, lacking the N-terminal methionine, however, proved highly suitable for the W6/32 based LOCI detection with BoLA-6*01301.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that N-terminus of β 2 m is involved in the formation of the W6/32 epitope (Shields and Ribaudo 1998) and in the case presented here, the N-terminal methionine of the recombinant bovine met-β 2 m likely interferes with W6/32 detection. Alternatively, the failed W6/32 recognition may be explained by the lack of pan-specificity of the antibody to BoLA-I when associated with bovine met-β 2 m (Joosten et al 1992). Substituting bovine met-β 2 m with human β 2 m, lacking the N-terminal methionine, however, proved highly suitable for the W6/32 based LOCI detection with BoLA-6*01301.…”
Section: Resultsmentioning
confidence: 99%
“…The vital nucleic acid stain Sytox Orange, which penetrates cells with compromised plasma membranes but will not cross uncompromised cell membranes, was added at 5 m (final) and incubated (10 min) prior to automated reading of results by twochannel fluorescence microscopy (Cell Observer, Carl Zeiss, x5, ZEN 2012 software). Positive (pan-MHC I-specific mAb; IL-A88; [28]) and negative (FCS) controls were included with each serum-cell combination, together with a complement control (no serum) and live cell control (no serum and heat-inactivated complement). Total cells (∼4000/sample) and dead cells were counted using a macro in Image-J software [29].…”
Section: Complement-dependent Cytotoxicity Assaymentioning
confidence: 99%